The Impact of Gadgets on Student Learning Outcomes: A Case Study in Indonesia Junior High School Students - Fadilla Aprianti; Popi Dayurni; Laksmi Evasufi Widi Fajari; Doni Pernanda; Ranny Meilisa (Peneliti.net, 2022)
This study aims to determine the effect of gadget the outcomes learning in Indonesia junior high school students. This research is a type of qualitative research using case study method. Data collection techniques using observation, interviews and documentation. Data analysis was consists of data reduction steps, data presentation and drawing conclusions. The results of this research show that : (1) The use of gadgets among junior high school students is not only used as a means of communication but there are some students who often play gadgets instead of studying; 2) The positive effect of using gadgets is that students are able to get information and communication easily while the negative effect of using gadgets is that students forget time to study so that it can have an effect on student outcomes learning. The conclusion is this study is that excessive use of gadgets will have an effect on student outcomes learning.